Hadal Mud Dragons: First Insight Into the Diversity of Kinorhyncha From the Atacama Trench - Grzelak, Katarzyna; Zeppilli, Daniela; Shimabukuro, Mauricio; Sørensen, Martin V. (Frontiers in Marine Science, 2021)
Deep-sea trenches are one of the last frontiers for deep-sea exploration and represent a large reservoir of undiscovered biodiversity. This applies in particular to organisms belonging to smaller-size classes, such as meiofauna. Among different meiofauna taxa, kinorhynchs represent a large gap in our knowledge about global marine biodiversity in general, but primarily in extreme deep-sea environments. Out of the more than 300 known mud dragon species, only a single species has ever been described from hadal depths (>6000 m), i.e., Echinoderes ultraabyssalis from the Kuril-Kamchatka Trench. The results presented in this paper are based on material collected during a research expedition in 2018 investigating the Atacama Trench environment. We provide a first overview and comparison of the diversity and abundance of mud dragons in the Atacama Trench, the adjacent abyssal plain and continental slope off Chile. The study revealed six species of Echinoderes. Of these, Echinoderes mamaqucha sp. nov. is described as a new species and morphological data of three undescribed species are given. Because of the low number of available specimens, we provide only a brief description of these three species, and comparison with their morphologically closest congeners, but formal descriptions are not given. Moreover, Echinoderes juliae and Echinoderes pterus were also recovered. Echinoderes juliae was described from the abyssal plain off Oregon and along the continental rise off California, at 2702 to 3679 m depth. Echinoderes pterus is known from the high Arctic, the North Atlantic, and the Mediterranean Sea, and has also been reported to show a wide bathymetric distribution, from 675 to 4403 m. Interestingly, E. mamaqucha sp. nov. dominated at the trench stations and it reached its highest abundance at the deepest station, at 8085 m water depth. The only other single individual that was found in the Atacama Trench was Echinoderes sp.1. The remaining four species were all found at the abyssal and slope stations. The obtained results seem to confirm previous hypotheses about geographic isolation of deep-sea trenches and relatively low connectivity with other habitats, reflected by limited diversity of sediment dwelling fauna, particularly in the deepest parts of trenches.